Massive Open Online Courses for continuing education for nursing professionals in Peru - Bendezu-Quispe, Guido (Escola de Enfermagem de Ribeirão Preto / Universidade de São Paulo, 2020)

(untitled) (Rev Lat Am Enfermagem)
to determine the global offer of Massive Open Online Courses (MOOCs) in health and nursing, and to know the characteristics of its content, for continuing education in nursing professionals in Peru. METHOD: exploratory study was carried out on the websites: Coursera, edX, FutureLearn, XuetangX and Udacity, Class Central and MOOC List. The courses were classified according to the five nursing areas recognized by the Peruvian College of Nurses (Colegio de Enfermeros del Perú, CEP). From each course, data was collected on institution and country of origin, hours per week and total duration in weeks, audio and subtitle language. RESULTS: a total of 654 courses in this modality are offered in health were found, covering the five areas contemplated by the Peruvian College of Nurses. Fourteen courses were specifically developed for nursing with an average duration of five weeks (3.2 hours per week of activities). Eleven came from Anglo-Saxon institutions, with content in English. Only two courses were offered in Spanish and one in Turkish. CONCLUSION: Massive Open Online Courses would be a useful tool for the continuing education of the Peruvian nurse given the wide offer, including some specifically for nurses, in the different areas of nursing. The content of the course is mostly in English. Expanding the range of languages or subtitles would facilitate the participation of a larger audience.